Short-Run Adjustments of an Individual Bank - Bryan, William R.; Carleton, Willard T. (Econometrica, 1967)
Most dynamic theories of the monetary policy mechanism, and reserve position doctrine in particular, specify a homogeneous banking system response to monetary policy actions. This article argues that the micro models of bank behavior implicit in these monetary theories remain untested and perhaps misspecified. An experimental model of a single bank's weekly balance sheet adjustments is specified and estimated with the purpose of improving the micro foundations of the theory of monetary dynamics.